Modernisasi Budidaya Maggot sebagai bentuk penerapan penanganan sampah Waste to Green Energy pada BUMDes Guwosari Maju Sejahtera, Pajangan, Bantul - Hadi Saputra; Anak Agung Putu Susastriawan; Renna Yanwastika Ariyana (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
BUMDes Guwosari Maju Sejahtera as a business entity managed by Guwosari Village through waste management, has one of the businesses, namely maggot cultivation. Currently, there are obstacles experienced by BUMDes Guwosari, namely the maggot sorting process still uses manual methods, so it requires more time, energy and resources. In addition, maggot is only sold in the form of live maggot (wet) which has a price range of 5000 to 10,000 per kilogram and if maggot is not sold, it will become pupae and adult flies. Providing a touch of modernization through a touch of TTG by making a sieving machine and roasting machine and developing a Website for the marketing process, is certainly what is needed at this time, where the existence of this technology will be able to improve the production process, selling power and marketing reach of maggot products. In addition, giving a new touch to the packaging of maggot products is also a step so that the products produced can become a brand identity owned by BUMDes.